Evaluation of a Recombinant Flavobacterium columnare DnaK Protein Vaccine as a Means of Protection Against Columnaris Disease in Channel Catfish (Ictalurus punctatus) - Lange, Miles D.; Abernathy, Jason; Farmer, Bradley D. (Frontiers in Immunology, 2019)
Flavobacterium columnare causes substantial losses among cultured finfish species. The Gram-negative bacterium is an opportunistic pathogen that manifests as biofilms on the host’s mucosal surfaces as the disease progresses. We previously demonstrated that the dominant mucosal IgM antibody response to F. columnare is to the chaperone protein DnaK that is found in the extracellular fraction. To establish the efficacy of using recombinant protein technology to develop a new vaccine against columnaris disease, we are reporting on two consecutive years of vaccine trials using a recombinant F. columnare DnaK protein (rDnaK). In year one, three groups of channel catfish (n=300) were immunized by bath immersion with a live attenuated F. columnare isolate, rDnaK or sham immunized. After six weeks, an F. columnare laboratory challenge showed a significant increase in survival (>30%) in both the live attenuated and rDnaK vaccines when compared to the non-immunized control. A rDnaK-specific ELISA revealed significant levels of mucosal IgM antibodies in the skin of catfish immunized with rDnaK at four and six weeksfour- and six-weeks post immunization. In the second year, three groups of channel catfish (n=300) were bath immunized with rDnaK alone or with rDnaK after a brief osmotic shock or sham immunized. After six weeks a laboratory challenge with F. columnare was conducted and showed a significant increase in survival in the rDnaK (> 25%) and in rDnaK with osmotic shock (>35%) groups when compared to the non-immunized control. The rDnaK-specific ELISA demonstrated significant levels of mucosal IgM antibodies in the skin of catfish groups immunized with rDnaK at four and six weeksfour- and six-weeks post immunization. To further understand the processes which have conferred immune protection in the rDnaK group, we conducted RNA sequencing of skin samples from the non-immunized (n=6) and rDnaK treated channel catfish at one-week (n=6) and six weeks (n=6) post immunization. Significantly altered gene expression was identified and results will be discussed. Work to further enhance the catfish immune response to F. columnare rDnaK is underway; as this protein remains a promising candidate for additional optimization and experimental trials in a production setting.